2008
DOI: 10.1164/rccm.200710-1589oc
|View full text |Cite
|
Sign up to set email alerts
|

Lung Stress and Strain during Mechanical Ventilation for Acute Respiratory Distress Syndrome

Abstract: Rationale: Lung injury caused by a ventilator results from nonphysiologic lung stress (transpulmonary pressure) and strain (inflated volume to functional residual capacity ratio). Objectives: To determine whether plateau pressure and tidal volume are adequate surrogates for stress and strain, and to quantify the stress to strain relationship in patients and control subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
542
7
34

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 674 publications
(619 citation statements)
references
References 40 publications
18
542
7
34
Order By: Relevance
“…In the study of Chiumello et al 10,. it was shown that stress values, based on esophagus pressure measurements, were 21.8 ± 5.4 and 13.3 ± 3.7 cmH 2 O at respectively 15 and 5 cmH 2 O of PEEP and tidal volume of 10 ml.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…In the study of Chiumello et al 10,. it was shown that stress values, based on esophagus pressure measurements, were 21.8 ± 5.4 and 13.3 ± 3.7 cmH 2 O at respectively 15 and 5 cmH 2 O of PEEP and tidal volume of 10 ml.…”
Section: Discussionmentioning
confidence: 95%
“…In the present study, we found 24.0 ± 2.7 and 13.1 ± 3.8 cmH 2 O in the lung disorder group at the same PEEP and tidal volume. In addition, Chiumello et al 10. showed that for patients with normal lungs, the stress values were 19.2 ± 3.2 and 10.9 ± 3.3 cmH 2 O at respectively 15 and 5 cmH 2 O of PEEP and tidal volume of 8 ml, whereas we found similar values: 21.3 ± 8.1 and 10.6 ± 4.7 cmH 2 O at the same PEEP and tidal volume.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, two different parameters describing the mechanical insult associated with ventilation have been proposed as actual determinants of VILI: lung stress, defined as the pressure developing within the lung fibrous skeleton, which equals the applied transpulmonary pressure [12], and lung strain, defined as the ratio between the lung volume variation (due to both V T and positive end-expiratory pressure, PEEP) and the lung resting volume [13]. In ARDS, we have recently shown that both V T expressed in relation to body weight and the airway pressure applied are ''inadequate surrogates'' for the evaluation of the actual lung stress and strain applied, due to a large variability in lung resting volume (functional residual capacity, FRC) and in chest wall mechanics [14]. Moreover, we have recently reported [15] that different mechanisms, such as the intratidal lung opening and closing, may be responsible for the lung injury associated with ventilation in ALI/ARDS, therefore questioning direct translation to humans of findings obtained from experimental settings regarding the role of an excessive V T and airway pressure.…”
Section: Introductionmentioning
confidence: 99%